The Feed Assessment Tool (FEAST) instructional design process - International Livestock Research Institute (International Livestock Research Institute, 2015)
The Feed Assessment Tool (FEAST) was created by CIAT and ILRI, with contributions over time from many other partners and users of the tool. It is a systematic method to assess local feed resource availability and use. This film is one of two that explain a FEAST learning initiative by ILRI and partners to promote and optimize use of the tool through different formats.